Economic and commercial convergence in Latin America. How are these countries doing so far? (2021)
This paper aims to analyze economic and commercial convergence in the three active integration agreements in the region: Central American Integration System, Southern Common Market, and Pacific Alliance. To this end, we estimated the Economic Convergence Index and correlations among the main macroeconomic aggregates. The empirical evidence reveals that, apart from Venezuela, Latin American countries have a high potential to form a common market. This potential derives more from the dynamics of their economies than from the political blocs or agreements that States want to pursue.